2016
DOI: 10.3390/su8080699
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Cultural Tourism in Urban Destinations: Does Space Matter?

Abstract: Policy makers and tourism developers must understand visitors' mobility behavior and how they consume space and tourism resources in order to set up sustainable cultural tourism destinations. With this in mind, it should also be pointed out that the mobility patterns of tourists in urban destinations are mainly located in the city center (spatial centrality), the analysis of which enables us to define "how central" the resources (museums, monuments, etc.) are and what the interactions between them are. Compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 38 publications
(40 reference statements)
1
47
0
1
Order By: Relevance
“…For example, Nicholas and Tsai indicated that sense of place directly and significantly affects residents' support for local tourism development [57], Ap and Lankford found that a stronger sense of place had a negative effect on residents' tourism development support [58,59], whereas several scholars did not find a significant and direct relationship between sense of place and tourism support [7,60].…”
Section: Sense Of Placementioning
confidence: 99%
See 1 more Smart Citation
“…For example, Nicholas and Tsai indicated that sense of place directly and significantly affects residents' support for local tourism development [57], Ap and Lankford found that a stronger sense of place had a negative effect on residents' tourism development support [58,59], whereas several scholars did not find a significant and direct relationship between sense of place and tourism support [7,60].…”
Section: Sense Of Placementioning
confidence: 99%
“…A total of 400 questionnaires were delivered, and 331 effective ones were recalled with a response rate of 82.75%, after eliminating those that were incomplete. This sample size was sufficient for performing the structural equation model (SEM) analysis [57].…”
Section: Questionnaire Design and Data Collectionmentioning
confidence: 99%
“…Although the boom in international tourism has undoubtedly generated many benefits, this growth has also begun to cause problems-the large number of visitors attracted by the main sights of tourist destinations has begun to be a concern for the representatives of the DMO (Destination Management Organizations) [284] . The representatives of the DMO must understand not only the movement of tourists in the destination but also the use of the space and tourism resources needed in order to be more sustainable [285]. Specifically, for the study of tourist behavior and therefore, their movement in space and time, there are no formally proposed methodologies but there are several tools that allow both data capture and the analysis of them.…”
Section: Discussionmentioning
confidence: 99%
“…It's also promoted on most health channels by providing a mental and physical well-being, sustaining the multilateral functionality of the body; goes hand in hand with the environment, promoting outdoor movement and helping to reduce pollution. Cycling is also related to the cultural development of society, cycling paths in Europe facilitating cultural exchanges and highlighting historical heritage; It's an economic engine generating a distinct manufacturing sector, requiring the construction of specific infrastructures (Aranburu Plaza, & Esteban, 2016), including the track corridors that cross Europe today, also contributing to the extremely beneficial exploitation of mountain resorts (Badau & Badau, 2018), including the use of climbing means; Because of cycling there are events with the participation of significant biker communities as well as great sporting events promoted at the highest international media level. While cycling infrastructures in most European countries form a more and more laborious network, crossing the continent in all directions, in Romania their development level is particularly low.…”
Section: Introductionmentioning
confidence: 99%